High-strength soluble bridge plug
By designing a high-strength soluble bridge plug structure, combining soluble polymer materials and soluble alloy materials, and forming a protective layer through microarc oxidation and organic spraying, the problem of existing bridge plugs being easily corroded in the downhole environment is solved, and higher mechanical properties and corrosion resistance are achieved, and the efficiency and safety of downhole operations are improved.
Patent Information
- Application Number
- CN202411937144.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing soluble bridge plugs are susceptible to corrosion in downhole environments, resulting in reduced mechanical properties and inability to effectively maintain functional integrity.
A high-strength soluble bridge plug structure including a central tube, a load bearing seat and a rubber cylinder is used. The rubber cylinder is made of soluble polymer material, and other structures are made of soluble alloy material, and a protective layer is formed by microarc oxidation and organic spraying.
It improves the mechanical properties and corrosion resistance of the bridge plug, ensures that it can be completely dissolved after fracturing operation, improves the production efficiency of underground operations, and reduces operation risks and costs.
Smart Images

Figure CN119754731A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soluble bridge plugs, in particular to a high-strength soluble bridge plug. Background Art
[0002] As one of the important tools for staged fracturing, the oil and gas well sealing layer structure bridge plug has the characteristics of accurate sealing position, few construction processes and short construction period. After the bridge plug is used to seal the oil and gas well, it is required to have good tensile strength and ductility. If it is necessary to continue the construction of the oil and gas well, the non-soluble bridge plug needs to be mechanically drilled through with special equipment, which has complicated procedures, inconvenient operation and easy pollution. The soluble bridge plug can dissolve by itself after the construction is completed, and no well-clearing operation is required, which is more efficient. Downhole soluble materials include degradable polymer materials, soluble aluminum alloys, soluble magnesium alloys and soluble composite materials. Magnesium and magnesium alloys have the advantages of low density, excellent electromagnetic shielding and good machinability, but they also have the disadvantages of high chemical activity and low strength, which makes the bridge plug structure easy to corrode in the downhole environment, resulting in reduced mechanical properties. The bridge plug contacts and reacts with external liquids before fracturing, which makes it lose its functional integrity. Therefore, we propose a high-strength soluble bridge plug. Summary of the invention
[0003] The object of the present invention is to provide a high-strength soluble bridge plug to solve the problems raised in the prior art.
[0004] To achieve the above object, the present invention provides the following technical solutions: a high-strength soluble bridge plug, comprising a center tube, a bearing seat and a rubber sleeve, wherein the bearing seat and the rubber sleeve are sleeved on the outer side wall of the center tube;
[0005] An upper push ring is arranged on one side of the rubber cylinder, and an upper slip is arranged on the side of the upper push ring facing away from the rubber cylinder;
[0006] An inner protective ring is arranged on the other side of the rubber cylinder, an outer protective ring is arranged on the side of the inner protective ring facing away from the rubber cylinder, a lower cone is arranged on the side of the outer protective ring facing away from the inner protective ring, a lower slip is arranged on the side of the lower cone facing away from the outer protective ring, and a lower joint is arranged on the side of the lower slip facing away from the lower cone.
[0007] Furthermore, the outer side walls of the upper push ring and the lower cone are conical surfaces.
[0008] Furthermore, the inner cone angles of the cone surfaces of the upper push ring and the lower cone are 10 to 20 degrees.
[0009] Furthermore, the inner side walls of the upper slip and the lower slip are movably connected to the outer side wall of the central pipe.
[0010] Furthermore, the outer side walls of the upper slip and the lower slip are both embedded with tooth buckles.
[0011] Furthermore, the tooth directions of the upper slip tooth buckle and the lower slip tooth buckle are opposite.
[0012] Furthermore, the side of the upper slip close to the rubber cylinder is matched with the conical surface of the upper push ring at an angle;
[0013] The side of the lower slip close to the rubber cylinder is matched with the conical surface angle of the lower cone.
[0014] Furthermore, the inner side wall of the bearing seat and the lower cone is fixedly connected to the outer side wall of the central tube by bolts.
[0015] Furthermore, the inner wall of the lower joint is connected to the outer wall of the central tube through threads.
[0016] Furthermore, a side of the upper push ring close to the rubber tube matches the shape of the rubber tube;
[0017] The side of the inner protective ring close to the rubber tube matches the shape of the rubber tube;
[0018] The side of the inner protective ring facing away from the rubber sleeve is matched with the side of the outer protective ring close to the rubber sleeve.
[0019] Furthermore, the outer diameters of the upper push ring, the inner guard ring, the outer guard ring and the lower cone are the same.
[0020] Further, in order of position, the structures sleeved on the outer wall of the central tube are: a bearing seat, an upper slip, an upper push ring, a rubber cylinder, an inner protective ring, an outer protective ring, a lower cone, a lower slip and a lower joint;
[0021] The inner diameter of the above structure matches the outer diameter of the center tube.
[0022] In the above technical solution, when the bridge plug is used, its lower joint is connected to the setting tool, transported to the predetermined position, and the setting procedure is started. The setting tool provides stress to move the center pipe, and the slips crawl along the conical surface (the upper slips crawl along the conical surface of the upper push ring, and the lower slips crawl along the conical surface of the lower cone). The outer teeth of the slips are anchored and engaged with the inner wall of the casing, and the rubber sleeve contacts the inner wall of the outer casing to form a reliable seal. When the setting stress reaches the shear value, the setting tool is separated from the bridge plug, and the setting tool is pulled out to complete the application of the bridge plug.
[0023] The double slip design with opposite tooth directions can effectively realize the bidirectional locking of the bridge plug and maintain the setting load. It can also maintain a good seal even if the pressure changes. The stability and reliability of the bridge plug are improved and the risk of leakage is reduced.
[0024] The upper push ring and inner guard ring that match the shape of the rubber cylinder, and the outer guard ring that matches the shape of the inner guard ring can provide good protection, so that the rubber cylinder is protected from the influence of the slippage of the center tube, alleviate external impact, reduce the stress on the upper and lower slips, and to a certain extent avoid the premature setting caused by obstruction of the bridge plug, thereby ensuring the reliability of the seal.
[0025] Furthermore, the rubber cylinder is made of a soluble polymer material; except for the rubber cylinder, other structures of the bridge plug are made of a soluble alloy material.
[0026] In the above technical solution, in the bridge plug structure, the material of the rubber cylinder is selected as a soluble polymer material, and the other structural materials are soluble alloy materials, so as to realize the fully soluble characteristics of the bridge plug. After the fracturing operation is completed, the fully soluble bridge plug can be completely dissolved, and the dissolved products are discharged from the wellhead together with the return fluid, which can effectively improve the production efficiency of downhole operations, reduce operation risks, and save time and labor costs.
[0027] Further, the soluble alloy material is magnesium alloy Mg-RE-TM;
[0028] RE (rare earth element) is a mixture of one or more of yttrium (Y), gadolinium (Gd), dysprosium (Dy), erbium (Er), holmium (Ho), and samarium (Sm);
[0029] TM (transition metal) is a mixture of one or more of aluminum (Al), zinc (Zn), nickel (Ni), and copper (Cu).
[0030] Furthermore, the soluble alloy material includes the following mass components: 7-9% aluminum (Al), 0.5-2.0% zinc (Zn), 0.02-0.40% nickel (Ni), 0.05-1.0% rare earth element (RE), and the balance is magnesium (Mg).
[0031] Furthermore, the soluble alloy material contains 2-6 wt% of hollow glass microspheres;
[0032] The soluble alloy material is prepared by the following process:
[0033] The alloy raw materials are melted, cooled to 580-600° C., stirred and hollow glass microspheres are added and mixed; the temperature is raised to 720-730° C., stirred for 50-75 seconds; poured; and heat treated.
[0034] Further, the melting temperature is 720-730°C;
[0035] The stirring speed when the hollow glass microspheres are added is 600-700 rpm; the stirring speed after heating is 500-600 rpm.
[0036] Furthermore, the heat treatment process conditions are: 510-530°C solution heat treatment for 8-12h; 180-200°C aging heat treatment for 12-24h.
[0037] In the above technical scheme, among the magnesium alloy components, aluminum plays an important role in the organizational properties of the magnesium alloy, and can form a solid solution with magnesium to play a role in solid solution strengthening. During the solidification process, hard and brittle phase magnesium-aluminum intermetallic chemicals will precipitate along the grain boundaries, thereby significantly improving the mechanical properties of the magnesium alloy. An appropriate amount of zinc can increase the potential of the magnesium alloy, reduce the adverse effects of impurities on its corrosion resistance, and improve the strength of the magnesium alloy. Zinc can also form an oxide film on the surface of the magnesium alloy, improve the corrosion resistance of the magnesium alloy, and alleviate the problem of reduced mechanical properties during use caused by corrosion of the bridge plug structure in the wellbore environment. Nickel can combine with aluminum to precipitate an aluminum-nickel phase, which is distributed and dispersed as a second phase, and can effectively improve the mechanical properties and solubility properties of the magnesium alloy. The addition of rare earth elements purifies the alloy matrix, improves the purity and corrosion resistance of the magnesium alloy, and can refine the grains and improve the strength and high temperature performance of the magnesium alloy.
[0038] Among them, the rare earth element yttrium has a high solid solubility in magnesium, and its crystal structure is the same as magnesium, which is hexagonal close-packed. By mismatching the atomic size and increasing the content of the low-melting-point phase at the grain boundary, the magnesium alloy can obtain second-phase strengthening at room temperature. And yttrium is highly active and can preferentially react with oxygen to form a composite rare earth oxide layer, which improves the corrosion resistance of the magnesium alloy, improves its surface stability, and has better protection against corrosion. At room temperature, yttrium forms an intermetallic compound with magnesium, which plays a role in dispersion strengthening; and it is distributed on the grain boundary, pinning the grain boundary, inhibiting grain boundary slip, hindering dislocation movement, and strengthening the alloy, so that the magnesium alloy has good high-temperature creep resistance.
[0039] Magnesium alloys also contain hollow glass microspheres, which are added to the magnesium alloy melt as hard glass particles, which can significantly improve the strength and hardness of the magnesium alloy and reduce the density of the magnesium alloy to a certain extent. It can also promote nucleation as a heterogeneous phase in the magnesium alloy, refine the magnesium alloy grains, and thus improve its mechanical properties. The addition of hollow glass microspheres increases the number of grain boundaries in the magnesium alloy and the crystal defects at the grain boundaries; at the same time, the hollow glass microspheres can hinder the formation of a continuous network structure of the magnesium-aluminum phase, alleviating the obstruction of the network magnesium-aluminum phase to the dissolution of the magnesium alloy. The magnesium element can react with the hollow glass microspheres on its surface to generate a magnesium-silicon phase, introducing more defects, making the magnesium alloy more susceptible to corrosion after fracturing operations.
[0040] As the first stage of heat treatment of magnesium alloy, solution heat treatment heats the dissolved elements to dissolve them in the magnesium alloy matrix, thereby improving the plasticity and toughness of the magnesium alloy; and during the treatment, the magnesium alloy grains are distorted, which strengthens its mechanical properties. Then, aging treatment is carried out to redistribute the dissolved elements to form a dispersed phase, thereby enhancing the strength and hardness of the magnesium alloy and achieving a balance between the solubility and mechanical properties of the soluble alloy material.
[0041] After the bridge plug operation is completed, fracturing operation is carried out. The soluble polymer materials and soluble alloy materials gradually dissolve under the immersion and erosion of the bottom hole fluid. The structures such as slips and rubber cylinders disintegrate and lose their anchoring ability. The bridge plug eventually falls off and unseals itself.
[0042] Furthermore, the soluble alloy material is subjected to surface treatment, which is micro-arc oxidation and organic spraying in sequence.
[0043] Furthermore, the process conditions of micro-arc oxidation are: current density 2 to 15 A / dm 2 , duty cycle 10-40%, duration 10-15min;
[0044] The electrolyte used in micro-arc oxidation includes the following components: 2-10 g / L potassium hydroxide, 10 g / L potassium fluoride, 10 g / L sodium silicate, and the electrolyte temperature is 20-40°C.
[0045] Further, organic spraying includes the following processes:
[0046] The surface of the oxide layer formed after micro-arc oxidation is heated to 130-150°C, sprayed with soluble resin coating, placed at 110-120°C, and baked for 20-30 minutes; cooled to 55-65°C, sprayed with polytetrafluoroethylene coating, placed at 380-400°C, and baked for 50-60 minutes to form an organic layer.
[0047] Furthermore, the soluble resin coating is a mixture of one or more of polyurethane, polylactic acid, polyglycolic acid, polylactic acid-glycolic acid copolymer, polycaprolactone, polysuccinate, polyethylene adipate, polyamide, and polyimide.
[0048] Furthermore, the spraying thickness of the soluble resin coating is 3 to 10 μm;
[0049] The spraying thickness of polytetrafluoroethylene coating is 5 to 12 μm.
[0050] In the above technical solution, surface treatment of the magnesium alloy can solve the problem of reduced mechanical properties caused by corrosion of the center pipe in the wellbore environment. First, micro-arc oxidation is performed to form an oxide layer on the surface of the magnesium alloy, which is composed of magnesium silicon oxide, magnesium aluminum oxide and magnesium oxide phase, and has good bonding strength with the magnesium alloy, and has high wear resistance and corrosion resistance. Then the temperature is increased to apply an organic coating (soluble resin coating, polytetrafluoroethylene coating) to form a protective film to prevent premature corrosion of the bridge plug; it can also reduce friction resistance, avoid the bridge plug from reacting with external liquids before fracturing, reduce the wear of the bridge plug during delivery, ensure its functional integrity, and ensure the self-degradation and peeling characteristics of the organic layer. The surface of the oxide layer has a complex porous structure, which can enhance the adhesion between the oxide layer and the organic layer and improve corrosion resistance.
[0051] Further, the soluble resin coating is prepared by the following process:
[0052] Mix the imido diacid monomer, diamine monomer and calcium chloride, add triphenyl phosphite and pyridine, dissolve in N-methylpyrrolidone, stir and heat to 120-125°C, and keep warm for 8-10 hours; cool to room temperature, dilute, add ethanol, filter, wash with ethanol, and vacuum dry; add deionized water, filter, wash with water, and vacuum dry to obtain a soluble resin;
[0053] Mix the soluble resin and emulsifier, heat to 40-60°C, and stir at 300-350rpm for 40-70min; add deionized water at a rate of 1 drop / s, and continue stirring at a constant temperature for 30min after adding; cool to obtain a soluble resin coating.
[0054] Furthermore, the diamine monomer is a mixture of one or more of 4,4-diaminodiphenyl ether, 3,7-diamino-2,8-dimethyldibenzothiophene sulfone, 1,3-bis(fluoro-aminophenyl)adamantane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline], and 1,3-bis(4-aminophenyl)adamantane.
[0055] Furthermore, the soluble resin includes the following components, calculated by mass ratio: 14.8 to 34.6 parts of imido diacid monomer, 4.0 to 10.6 parts of diamine monomer, 5.0 to 100 parts of calcium chloride, 24 to 24 parts of triphenyl phosphite, 10 to 100 parts of pyridine, and 80 to 100 parts of N-methylpyrrolidone.
[0056] Furthermore, the emulsifier is a mixture of one or more of cetyltrimethylammonium bromide, Span-80, Tween-80, and OP-10;
[0057] The amount of emulsifier used is 20-27% of the mass of the soluble resin;
[0058] The solid content of the soluble resin coating is 30-60%.
[0059] Further, the imido diacid monomer is prepared by the following process:
[0060] Mix 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene in dichloromethane, add carbon tetrachloride and triethylamine, heat to 40-50°C, reflux for 14-18h, distill under reduced pressure, wash, and dry to obtain an imide compound;
[0061] The imide compound, ethyl 2-methylacetoacetate and 1,4-diazabicyclo[2.2.2]octane are mixed in dichloromethane and stirred for reaction for 120 to 180 minutes; the dichlorohexane is removed by rotary evaporation, and the ethyl acetate compound is obtained by chromatography;
[0062] Stir and mix the ethyl acetate compound and triethylamine in acetonitrile for 100 to 120 minutes; cool to 0 to 3°C, slowly add the diacyl chloride, add within 30 minutes, and react for 120 to 150 minutes; add ice water, filter, let the filtrate stand, wash the organic phase, dry with anhydrous sodium sulfate, distill under reduced pressure, redissolve, filter, and distill under reduced pressure to obtain the acyl chloride compound;
[0063] Dissolve L-phenylalanine in a sodium hydroxide aqueous solution, cool to 0-2°C, add an acyl chloride compound, adjust the pH of the system to 8-10, and stir to react for 60-90 minutes; acidify, extract, dry with anhydrous magnesium sulfate, rotary evaporate, and vacuum dry to obtain an imido diacid monomer.
[0064] Further, the molar ratio of phosphazene, 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione, carbon tetrachloride, and triethylamine is 0.33:(1.1-1.2):(1.1-1.2):(1.1-1.2);
[0065] The ratio of phosphazene to dichloromethane is (4.5-5.5) g / 100 mL.
[0066] Further, the mass ratio of the imide compound, ethyl 2-methylacetoacetate, and 1,4-diazabicyclo[2.2.2]octane is 1:(0.69-0.76):(0.15-0.18);
[0067] The ratio of the imide compound to dichloromethane is (4 to 7) g / 100 mL.
[0068] Further, the diacid chloride is a mixture of one or more of terephthaloyl chloride, 4,4'-diacid diphenyl ether chloride, and 1,4-cyclohexanediyl chloride;
[0069] The mass ratio of ethyl acetate compound, diacyl chloride and triethylamine is 1:(0.6-0.9):(0.38-0.52);
[0070] The ratio of ethyl acetate compound to acetonitrile is (3-5) g / 100 mL.
[0071] Further, the mass ratio of the acyl chloride compound to L-phenylalanine is 1:(0.33-0.38);
[0072] The concentration of the sodium hydroxide aqueous solution is 0.2M;
[0073] The ratio of L-phenylalanine to the sodium hydroxide aqueous solution is (3.0 to 3.5) g / 100 mL.
[0074] In the above technical scheme, the soluble resin coating is obtained by emulsifying the soluble resin. The soluble resin is a polyamide-imide resin formed by the condensation reaction of an imide diacid monomer and a diamine monomer, which can be well bonded to the magnesium alloy and has good high temperature resistance, mechanical properties and chemical corrosion resistance, so that the high temperature pressure resistance of the prepared soluble alloy material is more excellent. And the soluble resin contains an ester group, which has strong permeability under hydrothermal conditions, can induce the transformation of the resin structure, so that it dissolves and hydrolyzes, and is degradable, and plays a role in fracturing corrosion. The diamine monomer can be a fluorine-containing diamine, which can reduce the surface energy of the soluble resin, improve its hydrophobicity, heat resistance, and stability, thereby improving its chemical and electrochemical resistance.
[0075] The imide diacid monomer is prepared from 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione, phosphazene, ethyl 2-methylacetoacetate, diacyl chloride and L-phenylalanine. The catechol in 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene reacts with two adjacent groups of chlorine groups to form a benzodioxaphosphorus structure. The reaction product contains an imide group and is recorded as an imide compound. It is mixed with ethyl 2-methylacetoacetate and undergoes a Michael addition reaction under the action of a base. The reaction product contains an ethyl acetate structure and is recorded as an ethyl acetate compound. It is mixed with diacyl chloride and its carbonyl group undergoes a nucleophilic substitution reaction. By controlling the ratio of the reactants, the reaction product contains an acyl chloride group and is recorded as an acyl chloride compound. It is reacted with an amino acid to finally obtain an imide diacid monomer. The structure of the imide diacid monomer contains rigid and high temperature resistant structures such as benzo heterocycle, imide, and aromatic group, which can improve the hardness and corrosion resistance of the prepared soluble resin. When applied to the surface of magnesium alloy, it can effectively improve the wear resistance and chemical corrosion resistance of the soluble alloy material, and its comprehensive performance can be maintained for a longer time in the underground environment.
[0076] Furthermore, the soluble polymer material includes the following components by mass: 60 to 80 parts of kneadable polyurethane rubber, 10 to 20 parts of nitrile rubber, 20 to 40 parts of soluble resin, 4 to 12 parts of vulcanizing agent, 50 to 80 parts of reinforcing phase, and 0.5 to 1.5 parts of auxiliary agent.
[0077] Furthermore, the reinforcing phase is a mixture of one or more of white carbon black, clay, montmorillonite, zinc oxide, carbon black, barium sulfate, and kaolin;
[0078] The curing agent is 2 to 4 parts of dicumyl peroxide (DCP) and 0.5 to 1.5 parts of triallyl isocyanurate (TAIC);
[0079] The auxiliary agent is stearic acid.
[0080] Furthermore, the soluble polymer material is prepared by the following process: preheating the kneadable polyurethane rubber, adding the reinforcing phase and the auxiliary agent in sequence for plasticization; adding the soluble resin, the vulcanizing agent and the auxiliary agent, mixing, kneading and vulcanizing to obtain the material.
[0081] Further, the preheating temperature is 50°C;
[0082] The process conditions for plasticizing are: temperature 70-100°C, time 3-5 minutes.
[0083] Furthermore, the mixing process conditions are: mixing temperature 110-130° C., mixing time 7-10 min; standing at room temperature for 3-24 h after mixing.
[0084] Furthermore, the process conditions of vulcanization are as follows: primary vulcanization: temperature 170-180°C, pressure 12-15MPa, time T90+3min; secondary vulcanization: temperature 150-160°C, time 3-4h.
[0085] In the above technical scheme, a soluble resin is added to the rubber sleeve material (soluble polymer material) for mixing and vulcanization to form a blending system, and a cross-linking network is constructed by an ester vulcanization reaction. While ensuring that the material can be degraded, the high temperature resistance, corrosion resistance, and mechanical properties of the soluble polymer material are effectively improved, the thermal and chemical stability of the soluble polymer material is improved, and the performance of the soluble polymer material in high temperature and corrosive media is maintained, so that it meets the sealing requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 This is a schematic diagram of the structure of a high-strength soluble bridge plug of the present invention;
[0087] Figure 2 It is a schematic diagram of the cross-sectional structure of a high-strength soluble bridge plug of the present invention.
[0088] In the figure, 1, center tube; 2, load-bearing seat; 3, upper cava; 4, upper push ring; 5, rubber cylinder; 6, inner protective ring; 7, outer protective ring; 8, lower cone; 9, lower cava; 10, lower joint. DETAILED DESCRIPTION
[0089] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] In the following specific implementations,
[0091] Mixed polyurethane rubber: MPU UR401, from Dongguan Huagong Fosu New Materials Co., Ltd.;
[0092] The vulcanizing agent is a mixture of diisopropylbenzene peroxide and triallyl isocyanurate, with a mass ratio of 3:1; the auxiliary agent is stearic acid;
[0093] The reinforcing phase is a mixture of white carbon black, zinc oxide, and carbon black N550, all of which are from Sinopharm Chemical Reagent Co., Ltd., with a mass ratio of 4:1:10;
[0094] Hollow glass microspheres: average particle size 12 μm, from Tiantai Jinggong Xili Glass Beads Co., Ltd.;
[0095] The emulsifier is a mixture of Span-80 and OP-10, with a mass ratio of 1:2;
[0096] Polyamide-imide resin: SI-307, from Kaifeng Quark New Materials Co., Ltd.;
[0097] Polytetrafluoroethylene coating: solid content is 60%, sourced from Japan Daikin Fluorochemical (China) Co., Ltd.;
[0098] The ratio of soluble resin to N,N-dimethylformamide is 10 g / 20 mL.
[0099] Example 1: Step 1, S1. Mix 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene in dichloromethane, add carbon tetrachloride and triethylamine, heat to 40°C, and reflux for 18 hours; distill under reduced pressure, wash, and dry to obtain an imide compound; the molar ratio of phosphazene, 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione, carbon tetrachloride, and triethylamine is 0.33:1.1:1.1:1.1; the ratio of phosphazene to dichloromethane is 4.5 g / 100 mL;
[0100] The imide compound, ethyl 2-methylacetoacetate and 1,4-diazabicyclo[2.2.2]octane were mixed in dichloromethane and stirred for reaction for 120 minutes; dichlorohexane was removed by rotary evaporation and chromatographed to obtain an ethyl acetate compound; the mass ratio of the imide compound, ethyl 2-methylacetoacetate and 1,4-diazabicyclo[2.2.2]octane was 1:0.69:0.15; the ratio of the imide compound to dichloromethane was 4 g / 100 mL;
[0101] Stir and mix the ethyl acetate compound and triethylamine in acetonitrile for 100 minutes; cool to 3°C, slowly add diacyl chloride, add within 30 minutes, and react for 120 minutes; add ice water, filter, let the filtrate stand, wash the organic phase, dry over anhydrous sodium sulfate, distill under reduced pressure, redissolve, filter, and distill under reduced pressure to obtain an acyl chloride compound; the diacyl chloride is terephthaloyl chloride; the mass ratio of ethyl acetate compound, diacyl chloride, and triethylamine is 1:0.6:0.38; the ratio of ethyl acetate compound and acetonitrile is 3g / 100mL;
[0102] Dissolve L-phenylalanine in 0.2M sodium hydroxide aqueous solution, cool to 2°C, add acyl chloride compound, adjust the system pH to 8, and stir to react for 90 minutes; acidify, extract, dry with anhydrous magnesium sulfate, rotary evaporate, and vacuum dry to obtain an imido diacid monomer; the mass ratio of acyl chloride compound to L-phenylalanine is 1:0.33; the ratio of L-phenylalanine to sodium hydroxide aqueous solution is 3.0 g / 100 mL;
[0103] S2. Mix the imide diacid monomer, the diamine monomer 4,4-diaminodiphenyl ether and calcium chloride, add triphenyl phosphite and pyridine, dissolve in N-methylpyrrolidone, stir and heat to 120°C, and keep the temperature for 10 hours; cool to room temperature, dilute, add ethanol, filter, wash with ethanol, and vacuum dry; add deionized water, filter, wash with water, and vacuum dry to obtain a soluble resin;
[0104] Mix the soluble resin, 20% emulsifier and N,N-dimethylformamide, heat to 40°C, and stir at 300 rpm for 70 minutes; add deionized water at a rate of 1 drop / s, and continue to stir at a constant temperature for 30 minutes after adding; cool, add ethanol for azeotropy, and add deionized water to obtain a soluble resin coating with a solid content of 30%;
[0105] Step 2, melting the alloy raw material at 720°C, cooling to 580°C, stirring at a speed of 700rpm and adding hollow glass microspheres to mix; heating to 720°C, stirring at a speed of 600rpm for 50s; pouring; heat treatment, the heat treatment process conditions are: 510°C solid solution heat treatment for 12h; 180°C aging heat treatment for 24h, to obtain a magnesium alloy; the magnesium alloy includes the following mass components: 7.77% aluminum, 1.26% zinc, 0.27% nickel, 0.15% yttrium, 2.1% hollow glass microspheres, and the balance is magnesium;
[0106] The magnesium alloy is placed in an electrolyte for micro-arc oxidation to form an oxide layer. The process conditions of micro-arc oxidation are: current density 2A / dm 2 , duty cycle 10%, duration 10min; the electrolyte includes the following components: 10g / L potassium hydroxide, 10g / L potassium fluoride, 10g / L sodium silicate, the electrolyte temperature is 30°C;
[0107] The surface of the magnesium alloy obtained in the previous step is heated to 130°C, sprayed with a soluble resin coating with a thickness of 5 μm, placed at 110°C, and baked for 20 minutes; cooled to 55°C, sprayed with a polytetrafluoroethylene coating with a thickness of 10 μm, placed at 380°C, and baked for 50 minutes to form an organic layer to obtain a soluble alloy material; used as a material for the bridge plug structure other than the rubber sleeve;
[0108] Step 3, preheat the mixed polyurethane rubber to 50°C, add the reinforcing phase and the additives in sequence, and plasticize at 70°C for 5 minutes; add the soluble resin, the vulcanizing agent, and the additives, mix and mix, and the mixing process conditions are: mixing temperature 110°C, mixing time 10 minutes; after mixing, let it stand at room temperature for 24 hours; vulcanize, and the vulcanization process conditions are: primary vulcanization: temperature 170°C, pressure 15MPa, time T90+3min; secondary vulcanization: temperature 150°C, time 3 hours, to obtain a soluble polymer material as a rubber cartridge material; the soluble polymer material includes the following mass components: 80 parts of mixed polyurethane rubber, 10 parts of nitrile rubber, 20 parts of soluble resin, 4 parts of vulcanizing agent, 50 parts of reinforcing phase, and 0.5 parts of additives;
[0109] Step 4: Arrange on the outer side wall of the central tube in sequence: a bearing seat, an upper slip, an upper push ring, a rubber sleeve, an inner guard ring, an outer guard ring, a lower cone, a lower slip and a lower joint to obtain a soluble bridge plug.
[0110] Example 2: Step 1, S1. Mix 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene in dichloromethane, add carbon tetrachloride and triethylamine, heat to 45°C, and reflux for 16 hours; distill under reduced pressure, wash, and dry to obtain an imide compound; the molar ratio of phosphazene, 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione, carbon tetrachloride, and triethylamine is 0.33:1.15:1.15:1.15; the ratio of phosphazene to dichloromethane is 5 g / 100 mL;
[0111] The imide compound, ethyl 2-methylacetoacetate, and 1,4-diazabicyclo[2.2.2]octane were mixed in dichloromethane and stirred for reaction for 150 minutes; dichlorohexane was removed by rotary evaporation, and ethyl acetate compound was obtained by chromatography; the mass ratio of the imide compound, ethyl 2-methylacetoacetate, and 1,4-diazabicyclo[2.2.2]octane was 1:0.72:0.16; the ratio of the imide compound to dichloromethane was 5 g / 100 mL;
[0112] Stir and mix the ethyl acetate compound and triethylamine in acetonitrile for 110 minutes; cool to 1°C, slowly add diacyl chloride, add within 30 minutes, and react for 135 minutes; add ice water, filter, let the filtrate stand, wash the organic phase, dry over anhydrous sodium sulfate, distill under reduced pressure, redissolve, filter, and distill under reduced pressure to obtain an acyl chloride compound; the diacyl chloride is 1,4-cyclohexanediyl chloride; the mass ratio of ethyl acetate compound, diacyl chloride, and triethylamine is 1:0.7:0.45; the ratio of ethyl acetate compound and acetonitrile is 4g / 100mL;
[0113] Dissolve L-phenylalanine in 0.2M sodium hydroxide aqueous solution, cool to 1°C, add acyl chloride compound, adjust the system pH to 9, and stir to react for 75 minutes; acidify, extract, dry with anhydrous magnesium sulfate, rotary evaporate, and vacuum dry to obtain an imido diacid monomer; the mass ratio of acyl chloride compound to L-phenylalanine is 1:0.35; the ratio of L-phenylalanine to sodium hydroxide aqueous solution is 3.2 g / 100 mL;
[0114] S2. Mix the imido diacid monomer, the diamine monomer 1,3-di(fluoro-aminophenyl)adamantane and calcium chloride, add triphenyl phosphite and pyridine, dissolve in N-methylpyrrolidone, stir and heat to 122°C, and keep the temperature for 9 hours; cool to room temperature, dilute, add ethanol, filter, wash with ethanol, and vacuum dry; add deionized water, filter, wash with water, and vacuum dry to obtain a soluble resin;
[0115] Mix the soluble resin, 24% emulsifier and N,N-dimethylformamide, heat to 50°C, and stir at 320rpm for 60min; add deionized water at a rate of 1 drop / s, and continue stirring at a constant temperature for 30min after adding; cool, add ethanol for azeotropy, and add deionized water to obtain a soluble resin coating with a solid content of 30%;
[0116] Step 2, melting the alloy raw material at 725°C, cooling to 590°C, stirring at a speed of 650rpm and adding hollow glass microspheres to mix; heating to 725°C, stirring at a speed of 550rpm for 60s; pouring; heat treatment, the heat treatment process conditions are: 520°C solid solution heat treatment for 102h; 190°C aging heat treatment for 18h, to obtain a magnesium alloy; the magnesium alloy includes the following mass components: 8.04% aluminum, 1.23% zinc, 0.31% nickel, 0.17% yttrium, 4.0% hollow glass microspheres, and the balance is magnesium;
[0117] The magnesium alloy is placed in an electrolyte for micro-arc oxidation to form an oxide layer. The process conditions of micro-arc oxidation are: current density 2A / dm 2, duty cycle 10%, duration 10min; the electrolyte includes the following components: 10g / L potassium hydroxide, 10g / L potassium fluoride, 10g / L sodium silicate, the electrolyte temperature is 30°C;
[0118] The surface of the magnesium alloy obtained in the previous step is heated to 140°C, sprayed with a soluble resin coating with a thickness of 5 μm, placed at 115°C, and baked for 25 minutes; cooled to 60°C, sprayed with a polytetrafluoroethylene coating with a thickness of 10 μm, placed at 390°C, and baked for 55 minutes to form an organic layer to obtain a soluble alloy material; used as a material for the bridge plug structure other than the rubber sleeve;
[0119] Step 3, preheat the mixed polyurethane rubber to 50°C, add the reinforcing phase and the additives in sequence, and plasticize at 85°C for 4 minutes; add the soluble resin, the vulcanizing agent, and the additives, mix and mix, and the mixing process conditions are: mixing temperature 120°C, mixing time 8 minutes; after mixing, let it stand at room temperature for 24 hours; vulcanize, and the vulcanization process conditions are: primary vulcanization: temperature 1750°C, pressure 14MPa, time T90+3min; secondary vulcanization: temperature 155°C, time 3.5h, to obtain a soluble polymer material as a rubber cartridge material; the soluble polymer material includes the following mass components: 70 parts of mixed polyurethane rubber, 15 parts of nitrile rubber, 30 parts of soluble resin, 8 parts of vulcanizing agent, 50 parts of reinforcing phase, and 1.0 part of additive;
[0120] Step 4: Arrange on the outer side wall of the central tube in sequence: a bearing seat, an upper slip, an upper push ring, a rubber sleeve, an inner guard ring, an outer guard ring, a lower cone, a lower slip and a lower joint to obtain a soluble bridge plug.
[0121] Example 3: Step 1, S1. Mix 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene in dichloromethane, add carbon tetrachloride and triethylamine, heat to 50°C, and reflux for 14 hours; distill under reduced pressure, wash, and dry to obtain an imide compound; the molar ratio of phosphazene, 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione, carbon tetrachloride, and triethylamine is 0.33:1.2:1.2:1.2; the ratio of phosphazene to dichloromethane is 5.5 g / 100 mL;
[0122] The imide compound, ethyl 2-methylacetoacetate, and 1,4-diazabicyclo[2.2.2]octane were mixed in dichloromethane and stirred for reaction for 180 minutes; dichlorohexane was removed by rotary evaporation, and ethyl acetate compound was obtained by chromatography; the mass ratio of the imide compound, ethyl 2-methylacetoacetate, and 1,4-diazabicyclo[2.2.2]octane was 1:0.76:0.18; the ratio of the imide compound to dichloromethane was 7 g / 100 mL;
[0123] Stir and mix ethyl acetate compound and triethylamine in acetonitrile for 120 minutes; cool to 0°C, slowly add diacyl chloride, add within 30 minutes, and react for 150 minutes; add ice water, filter, let the filtrate stand, wash the organic phase, dry over anhydrous sodium sulfate, distill under reduced pressure, redissolve, filter, and distill under reduced pressure to obtain an acyl chloride compound; the diacyl chloride is 4,4'-diacyl chloride diphenyl ether; the mass ratio of ethyl acetate compound, diacyl chloride, and triethylamine is 1:0.9:0.52; the ratio of ethyl acetate compound and acetonitrile is 5g / 100mL;
[0124] Dissolve L-phenylalanine in 0.2M sodium hydroxide aqueous solution, cool to 0°C, add acyl chloride compound, adjust the system pH to 10, and stir to react for 60 minutes; acidify, extract, dry with anhydrous magnesium sulfate, rotary evaporate, and vacuum dry to obtain an imido diacid monomer; the mass ratio of acyl chloride compound to L-phenylalanine is 1:0.38; the ratio of L-phenylalanine to sodium hydroxide aqueous solution is 3.5g / 100mL;
[0125] S2. Mix the imido diacid monomer, the diamine monomer 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and calcium chloride, add triphenyl phosphite and pyridine, dissolve in N-methylpyrrolidone, stir and heat to 125°C, and keep the temperature for 8 hours; cool to room temperature, dilute, add ethanol, filter, wash with ethanol, and vacuum dry; add deionized water, filter, wash with water, and vacuum dry to obtain a soluble resin;
[0126] Mix the soluble resin, 27% emulsifier and N,N-dimethylformamide, heat to 60°C, and stir at 350rpm for 40min; add deionized water at a rate of 1 drop / s, and continue stirring at a constant temperature for 30min after adding; cool, add ethanol for azeotropy, and add deionized water to obtain a soluble resin coating with a solid content of 30%;
[0127] Step 2, melting the alloy raw material at 730°C, cooling to 600°C, stirring at a speed of 600rpm and adding hollow glass microspheres to mix; heating to 730°C, stirring at a speed of 500rpm for 75s; pouring; heat treatment, the heat treatment process conditions are: 530°C solid solution heat treatment for 82h; 200°C aging heat treatment for 12h, to obtain a magnesium alloy; the magnesium alloy includes the following mass components: 7.93% aluminum, 1.30% zinc, 0.25% nickel, 0.18% yttrium, 5.9% hollow glass microspheres, and the balance is magnesium;
[0128] The magnesium alloy is placed in an electrolyte for micro-arc oxidation to form an oxide layer. The process conditions of micro-arc oxidation are: current density 2A / dm 2, duty cycle 10%, duration 10min; the electrolyte includes the following components: 10g / L potassium hydroxide, 10g / L potassium fluoride, 10g / L sodium silicate, the electrolyte temperature is 30°C;
[0129] The surface of the magnesium alloy obtained in the previous step is heated to 150°C, sprayed with a soluble resin coating with a thickness of 5 μm, placed at 120°C, and baked for 20 minutes; cooled to 65°C, sprayed with a polytetrafluoroethylene coating with a thickness of 10 μm, placed at 400°C, and baked for 60 minutes to form an organic layer to obtain a soluble alloy material; used as a material for the bridge plug structure other than the rubber sleeve;
[0130] Step 3, preheat the mixed polyurethane rubber to 50°C, add the reinforcing phase and the additives in sequence, and plasticize at 100°C for 3 minutes; add the soluble resin, the vulcanizing agent, and the additives, mix and mix, and the mixing process conditions are: mixing temperature 130°C, mixing time 7 minutes; after mixing, stand at room temperature for 24 hours; vulcanize, and the vulcanization process conditions are: primary vulcanization: temperature 180°C, pressure 12MPa, time T90+3min; secondary vulcanization: temperature 160°C, time 3 hours, to obtain a soluble polymer material as a rubber cartridge material; the soluble polymer material includes the following mass components: 60 parts of mixed polyurethane rubber, 20 parts of nitrile rubber, 40 parts of soluble resin, 12 parts of vulcanizing agent, 50 parts of reinforcing phase, and 1.5 parts of additives;
[0131] Step 4: Arrange on the outer side wall of the central tube in sequence: a bearing seat, an upper slip, an upper push ring, a rubber sleeve, an inner guard ring, an outer guard ring, a lower cone, a lower slip and a lower joint to obtain a soluble bridge plug.
[0132] Comparative Example 1: The magnesium alloy includes the following mass components: 7.83% aluminum, 1.28% zinc, 0.29% nickel, 0.14% yttrium, and the balance is magnesium;
[0133] The other processes are the same as those in Example 1 to obtain a soluble bridge plug.
[0134] Comparative Example 2: Step 1, heating the surface of the magnesium alloy obtained in the previous step to 130° C., spraying a soluble resin (polyamide-imide resin), baking, cooling, and spraying a polytetrafluoroethylene coating to obtain a soluble alloy material;
[0135] Step 2, the soluble polymer material includes the following mass components: 80 parts of mixed polyurethane rubber, 10 parts of nitrile rubber, 20 parts of soluble resin (polyamide-imide resin), 4 parts of vulcanizing agent, 50 parts of reinforcing phase, and 0.5 parts of auxiliary agent;
[0136] Step 3 is the same as step 4 in Example 1, and a soluble bridge plug is obtained.
[0137] Comparative Example 3: Step 1, heating the surface of the magnesium alloy obtained in the previous step to 55° C., spraying polytetrafluoroethylene coating to obtain a soluble alloy material;
[0138] Step 2, the soluble polymer material includes the following mass components: 80 parts of mixed polyurethane rubber, 10 parts of nitrile rubber, 4 parts of vulcanizing agent, 50 parts of reinforcing phase, and 0.5 parts of auxiliary agent;
[0139] Steps 2-3 are the same as steps 3-4 in Comparative Example 2 to obtain a soluble bridge plug.
[0140] Experiment: The soluble bridge plugs obtained in Examples 1-3 and Comparative Examples 1-3 were taken to prepare samples, and their performances were tested and the test results were recorded:
[0141] 1.Performance test for soluble alloy materials:
[0142] High temperature mechanical properties test: refer to standard GB / T 228, test the yield strength of the sample at 150℃;
[0143] Brinell hardness test: Use Brinell hardness tester to test the Brinell hardness of the sample, the indenter diameter is 5mm, the pressure is 250kgf, the holding time is 30s, Φ28mm×3mm,
[0144] Corrosion resistance test: The electrochemical performance was tested by an electrochemical workstation. The working electrode was the sample, with a size of Φ28mm×3mm, the counter electrode was platinum, the reference electrode was saturated silver chloride, the electrolyte was 3wt% potassium chloride solution, the experimental temperature was 25°C, and the scanning rate was 0.5mV / s.
[0145] Dissolution rate test: Place the magnesium alloy in a 3wt% potassium chloride solution at 80°C and test the dissolution rate of the sample;
[0146] Table 1. Performance test results of soluble alloy materials:
[0147]
[0148] According to the data in the above table, we can clearly draw the following conclusions:
[0149] The soluble bridge plugs obtained in Examples 1-3 are compared with the soluble bridge plugs obtained in Comparative Examples 1-3. The test results show that:
[0150] Compared with the comparative example, the soluble alloy material of the soluble bridge plug obtained in Examples 1-3 has higher high temperature yield strength, Brinell hardness, dissolution rate data and lower self-corrosion current density data, and the higher hardness makes the alloy more difficult to be scratched. This fully demonstrates that the present invention achieves high temperature mechanical properties, wear resistance and corrosion resistance of the soluble alloy material, and has good fracturing dissolution ability.
[0151] Compared with Example 1, the magnesium alloy in Comparative Example 1 does not add hollow glass microspheres, which significantly reduces the high temperature strength and hardness of the magnesium alloy, reduces the structural defects, and weakens the dissolution ability of the alloy. The intermetallic compound formed by the hollow glass microspheres and the magnesium alloy can improve its corrosion resistance to a certain extent, but it will also produce defects after micro-arc oxidation, reduce the bonding strength between the oxide layer and the organic layer, and affect the corrosion resistance. Therefore, the self-corrosion current density of the soluble alloy material in Comparative Example 1 does not change significantly.
[0152] The soluble resin in Comparative Example 2 is a commercially available polyamide-imide resin and is applied to the soluble alloy material, while no soluble resin is provided in the soluble alloy material of Comparative Example 3. This significantly deteriorates the self-corrosion current density data of the soluble alloy material.
[0153] 2.Performance test of soluble polymer materials:
[0154] Mechanical properties test: refer to standard GB / T 528, test the tensile strength of the sample, tensile speed 500mm / min;
[0155] Thermal stability test: Place the sample in 100℃ tap water, soak for 24 hours, then take it out and test the mechanical properties of the sample again, and calculate the strength retention rate of the sample after the experiment;
[0156] Corrosion resistance test: Place the sample in a pure alkali solution with a pH of 12, stir at 85°C for 12 hours, take it out and wipe it dry with filter paper, and calculate the mass loss rate of the sample after the experiment;
[0157] Table 2. Performance test results of soluble polymer materials:
[0158] Soluble polymer materials Tensile strength(MPa) Strength retention rate (%) Mass loss rate (%) Example 1 29.7 57.8 0.37 Example 2 29.5 62.2 0.31 Example 3 30.5 65.9 0.21 Comparative Example 2 27.8 35.4 0.50 Comparative Example 3 23.6 27.3 0.74
[0159] According to the data in the above table, we can clearly draw the following conclusions:
[0160] The soluble bridge plugs obtained in Examples 1-3 are compared with the soluble bridge plugs obtained in Comparative Examples 1-3. The test results show that:
[0161] Compared with the comparative example, the soluble polymer material of the soluble bridge plug obtained in Examples 1-3 has higher tensile strength, strength retention rate data and lower mass loss rate, which fully demonstrates that the present invention achieves the improvement of mechanical properties, high temperature resistance and corrosion resistance of the soluble polymer material.
[0162] Compared with Example 1, the soluble resin in Comparative Example 2 is a commercially available polyamide-imide resin, and is applied to the soluble polymer material; and no soluble resin is provided in the soluble polymer material of Comparative Example 3. This significantly deteriorates the tensile strength, strength retention rate, and mass loss rate data of the soluble resin.
[0163] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A high-strength soluble bridge plug, characterized in that: It comprises a central tube (1), a bearing seat (2) and a rubber tube (5), wherein the bearing seat (2) and the rubber tube (5) are sleeved on the outer side wall of the central tube (1); An upper push ring (4) is provided on one side of the rubber cylinder (5), and an upper slip (3) is provided on the side of the upper push ring (4) facing away from the rubber cylinder (5); An inner protective ring (6) is arranged on the other side of the rubber cylinder (5); an outer protective ring (7) is arranged on the side of the inner protective ring (6) facing away from the rubber cylinder (5); a lower cone (8) is arranged on the side of the outer protective ring (7) facing away from the inner protective ring (6); a lower cava (9) is arranged on the side of the lower cone (8) facing away from the outer protective ring (7); and a lower joint (10) is arranged on the side of the lower cava (9) facing away from the lower cone (8).
2. A high-strength soluble bridge plug according to claim 1, characterized in that: The upper push ring (4) and the lower cone (8) have a conical surface on the side facing away from the rubber cylinder; The side of the upper slip (3) close to the rubber cylinder is matched with the conical surface of the upper push ring (4) at an angle; The side of the lower slip (9) close to the rubber cylinder is matched with the conical surface of the lower cone (8) at an angle.
3. A high-strength soluble bridge plug according to claim 1, characterized in that: The outer side walls of the upper slip (3) and the lower slip (9) are both embedded with tooth buckles.
4. A high-strength soluble bridge plug according to claim 2, characterized in that: The inner cone angle of the cone surface of the upper push ring and the lower cone is 10 to 20 degrees.
5. A high-strength soluble bridge plug according to any one of claims 1 to 4, characterized in that: The rubber cylinder is made of soluble polymer material; except for the rubber cylinder, other structures of the bridge plug are made of soluble alloy material.
6. A high-strength soluble bridge plug according to claim 5, characterized in that: The soluble alloy material comprises the following mass components: 7-9% aluminum, 0.5-2.0% zinc, 0.02-0.40% nickel, 0.05-1.0% rare earth elements, 2-6% hollow glass microspheres, and the balance is magnesium.
7. A high-strength soluble bridge plug according to claim 5, characterized in that: The soluble alloy material is subjected to surface treatment, which is micro-arc oxidation and organic spraying in sequence; Organic spraying includes the following processes: The surface of the oxide layer formed after micro-arc oxidation is heated to 130-150°C, sprayed with soluble resin coating, placed at 110-120°C, and baked for 20-30 minutes; cooled to 55-65°C, sprayed with polytetrafluoroethylene coating, placed at 380-400°C, and baked for 50-60 minutes to form an organic layer.
8. A high-strength soluble bridge plug according to claim 7, characterized in that: The soluble resin coating is prepared by the following process: Take the imido diacid monomer, diamine monomer and calcium chloride, mix them, add triphenyl phosphite and pyridine, dissolve them in N-methylpyrrolidone, stir and heat to 120-125°C, keep the temperature for 8-10 hours to obtain a soluble resin; mix the soluble resin, emulsifier and deionized water, stir to obtain a soluble resin coating.
9. A high-strength soluble bridge plug according to claim 8, characterized in that: The imido diacid monomer is prepared by the following process: Mix 1-(3,4-dihydroxyphenyl)-pyrrole-2,5-dione and phosphazene in dichloromethane, add carbon tetrachloride and triethylamine, heat to 40-50°C, and reflux for 14-18h to obtain an imide compound; The imide compound, ethyl 2-methylacetoacetate and 1,4-diazabicyclo[2.2.2]octane are mixed in dichloromethane and stirred for reaction for 120 to 180 minutes to obtain an ethyl acetate compound; Stir and mix the ethyl acetate compound and triethylamine in acetonitrile for 100 to 120 minutes; cool to 0 to 3°C, slowly add diacyl chloride, add within 30 minutes, and react for 120 to 150 minutes to obtain an acyl chloride compound; Dissolve L-phenylalanine in a sodium hydroxide aqueous solution, cool to 0-2° C., add an acyl chloride compound, adjust the pH of the system to 8-10, and stir the reaction for 60-90 minutes to obtain an imido diacid monomer.
10. A high-strength soluble bridge plug according to claim 9, characterized in that: The soluble polymer material comprises the following components by weight: 60 to 80 parts of mixed polyurethane rubber, 10 to 20 parts of nitrile rubber, 20 to 40 parts of soluble resin, 4 to 12 parts of vulcanizing agent, 50 to 80 parts of reinforcing phase, and 0.5 to 1.5 parts of auxiliary agent.
Citation Information
Patent Citations
Degradable polyamide imide / silicon dioxide nano composite material derived from L-amino acid and preparation method thereof
CN107141489A
Shaped material for downhole tool member, downhole tool member, and downhole tool
CN108368572A
Preparing method of high-strength high-conductivity thin film based on polyamide imide
CN109135279A
Magnesium-based metal-soluble bridge plug
CN109236230A
Soluble bridge plug
CN109899028A